The Good That Lawyers Do - Kathleen M. Sullivan (Washington University Journal of Law & Policy, 2000)
My topic is the good that lawyers do. This Essay provides a set of arguments for law students who are coming into this noble calling, this important profession. The essay offers a kind of booster shot, inoculation, or vaccination against every relative, classmate from college, or taxi driver who gives you a hard time about being a lawyer.
Keywords: Lawyers; Legal assistance to the poor; Social responsibility